Diabetic Cardiomyopathy: Cause or Consequence of Diabetes Mellitus? - A, Maria Luz Gunturiz; Chaparro, Pablo (Cardiology and Cardiovascular Medicine, 2017)
The pathogenesis of diabetic cardiomyopathy (DC) is not understood completely. DC is an important complication of longstanding diabetes that is associated with high mortality and morbidity rates, being its progression controlled by multiple factors. Within the mechanisms that have been proposed for DC are included metabolic and microvascular disorders, insulin resistance, myocardial fibrosis and cardiac autonomic dysfunction, among others. Its suggested that the Chronic hyperglycemia play an important role in the development of DC although multiple complex mechanisms and interplay of many molecular and metabolic events within the myocardium they could be involved with the pathogenesis. Some of the metabolic disorders associated with diabetes are hyperlipidemia, hyperglycemia and inflammation, which promote the formation of reactive species of oxygen and nitrogen, or other free radicals that induce the increase of diabetic nephropathy and cardiomyopathy. Several adaptive responses caused by the metabolic alterations mentioned, trigger cardiovascular disorders including heart failure. In this article, we review some of the animal models and molecular mechanisms potentially implicated in the progression of DC. In this article, we review some of the animal models and molecular mechanisms potentially implicated in the progression of DC.